Cultural Transformation in Healthcare: How Well Does the Veterans Health Administration Vision for Whole Person Care Fit the Needs of Patients at an Academic Rehabilitation Center? - Jessica L Barnhill MD, MPH; Isabel J Roth DrPH; Keturah R Faurot PhD, PA; Gilson D Honvoh MSPH; Chanee E Lynch MPH; Karla L Thompson PhD; Susan A Gaylord PhD (SAGE Publishing, 2022)
Background The Veterans Health Administration is undergoing a cultural transformation toward person-driven care referred to as the Whole Health System of Care. Objective This pilot study evaluated whether the Whole Health model resonates with patients of a large public university rehabilitation clinic. Methods Thirty participants completed the Veterans Health Administration's Personal Health Inventory (PHI), and six attended the course "Taking Charge of My Life and Health." Researchers analyzed PHI responses and post-course focus group transcripts. A short post-PHI survey and post-course evaluation were collected. Results Participants agreed the PHI is a simple, useful tool. The course, while well attended, did not meet participants' expectations. Participants wanted access to integrative therapies and opportunities to contribute to healthcare transformation. Conclusion Rehabilitation patients resonated with the Whole Health vision. They expressed enthusiasm for the cultural transformation represented by the model along with frustration that standard healthcare experiences fall short of this vision.